IMPLEMENTATION OF TAHFIDZ PROGRAM USING BAGHDADIYAH METHOD IN FORMING STUDENTS CHARACTER - Susetiyo, Ari; Abrahem Masuwd, Mowafg; Husna, Ismatul (Al-Ashr : Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
This study discusses the method of Bagdadiyah in tahfidz program at SDIT Al-Azhar. Today's students mostly just memorize it because of the demands of the school in fact the lack of formation of the character of responsibility in children. Based on the description above, the purpose of this study is to determine the initial preparation of tahfidz program baghdadiyah method, second to determine the implementation of tahfidz program baghdadiyah method in shaping the character of bilingual students responsibility SDIT Al-Azhar kediri, this study uses a qualitative approach type. Data sources in this study using primary data and secondary data. This study uses data analysis techniques such as data reduction, data presentation and Conclusion. The results of this study is to conclude that the tahfidz program baghdadiyah method in forming the character of responsibility has been formed through routine habits that are carried out every day such as deresan, murojaah.